2006
DOI: 10.1590/s0100-67622006000300018
|View full text |Cite
|
Sign up to set email alerts
|

Composição florística de um trecho de cerradão e cerrado sensu stricto e sua relação com o solo na floresta nacional (FLONA) de Paraopeba, MG, Brasil

Abstract: RESUMO -O presente trabalho foi realizado na FLONA de Paraopeba, MG, e teve como objetivo o levantamento florístico das fanerófitas, ao longo de um gradiente de cerradão e cerrado sensu stricto, em uma área de 2.600 m 2 . Foram encontradas 91 espécies, pertencentes a 71 gêneros de 41 famílias. As famílias mais representativas foram Leguminosae, Myrtaceae, Malpighiaceae, Vochysiaceae, Rubiaceae e Melastomataceae. Os gêneros Miconia, Myrcia, Erythroxylum e Qualea foram os mais ricos. Magonia pubescens destacou-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
3
1
0
8
Order By: Relevance
“…The high representivity of just a few species in terms of their numbers of individuals and their importance values, as seen in the present study, is often observed in woody savanna communities of typical cerrado (Felfili & Silva Júnior 1993, Cardoso et al 2002, Campos et al 2006) and rocky outcrop cerrado (Amaral et al 2006, Viana & Lombardi 2007). There were, however, marked differences between the 10 most important species in the two cerrado communities, with only Qualea parviflora being of marked structural importance in both TC and RC sites.…”
Section: 85supporting
confidence: 78%
“…The high representivity of just a few species in terms of their numbers of individuals and their importance values, as seen in the present study, is often observed in woody savanna communities of typical cerrado (Felfili & Silva Júnior 1993, Cardoso et al 2002, Campos et al 2006) and rocky outcrop cerrado (Amaral et al 2006, Viana & Lombardi 2007). There were, however, marked differences between the 10 most important species in the two cerrado communities, with only Qualea parviflora being of marked structural importance in both TC and RC sites.…”
Section: 85supporting
confidence: 78%
“…In addition, close to those found in studies in the formation of Cerradão (CAMPOS et al, 2006;RODRIGUES & ARAÚJO 2013). The CCA correlated Copaifera langsdorffii, Tapirira guianensis,Schefflera morototoni with soils of higher fertility and high aluminum content according to other studies of species distribution in the Seasonal Forest (DALANESI et al, 2004;TEIXEIRA & ASSIS, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…As famílias botânicas mais expressivas em relação à riqueza foram: Fabaceae (34%) seguida de Anonnaceae (8,5%) e Anacardiaceae (6,5%) perfazendo 49% de todos os indivíduos amostrados. Fabaceae é uma das quatro famílias mais representativas da flora mundial e, no Cerrado, sua representatividade já foi reportada por trabalhos de diversos autores como Goodland (1970), Balduino et al, (2005), Campos et al (2006), Ssouza et al 2008, Souza et al (2010), Ferreira et al (2014) e Giacomo et al, (2015). A família Annonaceae é uma das mais ricas em número de espécies (CHATROU et al 2004), e não costuma figurar dentre as mais representativas em levantamentos pelo Cerrado, sendo mais abundante no bioma Amazônico (MAAS et al 2012).…”
Section: Resultsunclassified